Spray-processed nanoporous BiVO4 photoanodes with high charge separation efficiency for oxygen evolution - Xi Chen; Dan Wang; Yu Huang; Yang Zhang; Chuang Li; Shaotong Wang; Yichun Liu; Xintong Zhang (APL Materials, 2020)
Spray pyrolysis is a convenient method for fabricating BiVO4 photoanondes from a precursor solution. As the precursor solution of spray pyrolysis can significantly influence the nanostructure and the amount of oxygen vacancies of the final films, modifying the precursor solution is an efficient strategy for improving the photoelectrochemical (PEC) performance of BiVO4 photoanodes. Herein, an ultraviolet and ultrasonic treatment for modifying a vanadium precursor solution of spray pyrolysis was developed to produce efficient nanoporous BiVO4 photoanodes. By the simple treatment, the AM 1.5 photocurrent density of the photoanode reached 1.76 mA/cm2 at 1.23 V vs the reversible hydrogen electrode (RHE) for water oxidation, which is 12.3 times higher than the untreated BiVO4 photoanode. The good PEC performance was mainly attributed to the excellent charge separation that reached approximately 94.2% at 1.23 V vs RHE. Systematic studies revealed that the treatment for the precursor solution could tune the nanoporous structure and increase the amount of oxygen vacancies in the final films. This finding offers a facile and effective approach for fabricating efficient photoelectrodes for PEC water splitting.